Pemberdayaan Ekonomi Berbasis Syariah Pada Muallaf Dayak Meratus Di Dusun Papagaran - Rozzana Erziaty; Agus Purnomo; Umi Hani; Abdul Wahab (Universitas Lancang Kuning, 2021)
Papagaran is located in Patikalain Village Hantakan Sub-District Hulu Sungai Tengah Regency, which is located in the mountains of Meratus, the majority religion at animism. People who are new to Islam are called Muallaf, thay ara still need help in adapting to their new conditions, whether material, knowledge or social assistance that will protect and strengthen their hearts to embrace for Islam. The purpose of the Community Empowerment Program (PPM) is to strengthen understanding of Islam in the economic field in accordance with regional potential, that are to provide assistance in the management of production, marketing and financial of agricultural products based on sharia. The method used by Rural Apracial Participatory. The population is the perpetrators of Dayak meratus farming of 27 people. The activity was carried out in December 2019. The cognitive assessment results of the PPM pretest participants were 96.3% less 3.7% and 0% good category. The posttest was less than 0%, the category was 55.6% and the good category was 44.4%. The result of the t-test was accepted Hi, namely an increase in the knowledge and skills of participants in the community empowerment training.